(untitled) (Global Journal of Human-Social Science, 2017)
The development of self-regulation in early childhood students is imperative for the development of higher level thinking skills. Thus, the ability to self-regulate has been link to academic achievement and as a better indicator of school readiness. However, the research does not look into culture or Cultural factorsas a variable that may influence the development of self-regulation. Minority students such as Latino and African Americans are considered to be at a higher risk for not developing these regulatory skills. Hence, this research looks at the associations between early childhood students, self-regulation, academics, and culture. Specifically, the research analyzes results from candidates that were either Latino American culture and African American culture.